La politique des "sites naturels" classés dans les Pyrénées : rétrospective des applications et enjeux contemporains - Johan Milian (Unité Mixte de Recherche 8504 Géographie-cités, 2007)
In France, the “natural sites” policy has constituted a framework feature for landscape protection that was very used in rural areas. This article surveys how this policy, little known by the broad public and currently considered as not very effective, was used in the Pyrenees mountain. In fact, this policy was a real milestone in the history of nature conservancy in these mountains. The article underlines that the “natural site” tool was rather relevant against the claims of industrious programs (dams and hydroelectric plants implementation) but it was less effective in monitoring the expansion of tourism and mountain urbanization. Moreover, its implementation needed early local acceptance: local decision makers and stakeholders tried monitoring its enforcement. Nowadays this policy seems obsolete because of its weak management capacity and because sometimes it was canted by certain influential players. Its effectiveness depends on each local context. The working of the feature also reflects important differences due to its provincial bulk-heading. However, the initiatives established around this feature enabled it to regulate the environmental and socioeconomic conflicts related to land use in mountain area. In fact, mountain stakeholders and environmental players used the “natural sites” framework as a place of discussion and negotiation for mountain regional planning action. This experience benefits further nature conservancy projects.